ANALISIS PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PENGGUNA JASA JAMAAH UMROH TAHUN 2010-2012 (STUDI KASUS PADA PT FATIMAH ZAHRA SEMARANG) - Nityasari, Aulia Hayu; Sutopo, Sutopo (Faculty of Economics and Business Diponegoro University, 2013)
Quality of services is consumer response to consumed services. Good or poor quality of service depends on the ability of the companies to meet customer expectations consistently. If it applied correctly, quality of service will create customer satisfaction toward to the services.The goals of this research to know an influence of the five dimensions of service quality that are reliability, responsiveness, assurance, emphaty, and tangibles to customer satisfaction in using service. This research gets primary data using questionnaires from PT Fatimah Zahra Semarang during 2010-2012.The Results of multiple regression analysis is Y = 0.243X1 + 0.367X2 + 0.157X3 + 0.221X4 + 0.182X5 . The most influential variable of independent variables is responsiveness with (β = 0.367). The next sequence are reliability (β = 0.243); emphaty (β = 0,221); tangibles (β = 0.182), and the last is assurance (β = 0,157). T test result proved that all independent variable (reliability, responsiveness, assurance, emphaty, and tangibles) have a positive influence on the dependent variable, customer satisfaction. The determinant coefficient adjusted R2 is 0,731, means 73,1% of customer satisfaction is affected by the variable reliability, responsiveness, assurance, emphaty, and tangibles. The balance of 26,9% is affected by other variable